Inside Back Cover. (27th March 2019) - Panicker, Seema; Ahmady, Islam M.; Almehdi, Ahmed M.; Workie, Bizuneh; Sahle‐Demessie, Endalkachew; Han, Changseok; Chehimi, Mohamed M.; Mohamed, Ahmed A.
Abstract : The cover image is based on the Full Paper Gold‐Aryl nanoparticles coated with polyelectrolytes for adsorption and protection of DNA against nuclease degradation by Seema Panicker et al., https://doi.org/10.1002/aoc.4803 . Design Credit: Abdallah Mouselly, Architecture Department, University of Sharjah.